Symptom appraisal and healthcare-seeking for symptoms suggestive of colorectal cancer: a qualitative study. Issue 10 (9th October 2015) - Hall, N; Birt, L; Banks, J; Emery, J; Mills, K; Johnson, M; Rubin, G P; Hamilton, W; Walter, F M
Abstract : Objectives: Timely diagnosis of colorectal cancer is important to improve survival. This study explored symptom appraisal and help-seeking among patients referred to specialist services with symptoms of colorectal cancer. Design: Qualitative in-depth interview study. Setting and participants: Participants were recruited on referral to gastroenterology clinics (North East and East of England); interviews were conducted soon after referral. We purposively sampled participants to ensure a range of accounts in terms of age, sex, diagnosis and geographical location. Methods: Data collection and analysis were underpinned by the Model of Pathways to Treatment. Framework analysis was used to explore the data within and across cases, focusing on patient beliefs and experiences, disease factors and healthcare influences. Results: 40 participants were interviewed (aged 43–87 years, 17 women, 18 diagnosed with colorectal cancer). Patients diagnosed with and without colorectal cancer had similar symptom pathways. We found a range of interacting and often competing biopsychosocial, contextual and cultural influences on the way in which people recognised, interpreted and acted on their symptoms. People attempted to 'maintain normality' through finding benign explanations for their symptoms. Bodily changes were appraised within the context of usual bowel patterns, comorbidities and life events, and decisions to seek help were made in relation to expectations about the course of symptoms. The 'private nature' of colorectal cancer symptoms could affect both their identification and discussions with others including healthcare professionals. Within the context of the National Health Service, people needed to legitimise appropriate use of healthcare services and avoid being thought of as wasting doctors' time. Conclusions: Findings provide guidance for awareness campaigns on reducing stigma around appraising and discussing bowel movements, and the importance of intermittent and non-specific symptoms. Altering perceptions about the appropriate use of health services could have a beneficial effect on time to presentation.